Electroformation of giant unilamellar vesicles on stainless steel electrodes - Pereno,V; Carugo,D; Bau,L; Sezgin,E; Bernardino,de la Serna J; Eggeling,C; Stride,E (ACS Omega, 2017)
Giant unilamellar vesicles (GUVs) are well-established model systems forstudying membrane structure and dynamics. Electroformation, also referred to aselectroswelling, is one of the most prevalent methods for producing GUVs, as it enablesmodulation of the lipid hydration process to form relatively monodisperse, defect-freevesicles. Currently, however, it is expensive and time-consuming compared with othermethods. In this study, we demonstrate that 1,2-dioleoyl-sn-glycero-3-phosphatidylcholine GUVs can be prepared readily at a fraction of the cost on stainless steel electrodes,such as commercially available syringe needles, without any evidence of lipid oxidationor hydrolysis.